In vivo resuscitation, perfusion, and transplantation of a porcine cardiac allograft donated after circulatory death. Issue 2 (25th November 2019) - Grant, April A.; Klima, Alan; Duenas, Alejandro; Gardiner, Amy; Thomas, Maeghan; Badiye, Amit; Vianna, Rodrigo; Loebe, Matthias; Ghodsizad, Ali
Abstract: Objectives: To test the feasibility of a novel method of heart donation under circulatory death criteria that allows precardiectomy donor heart assessment. Materials and methods: This is a translational study utilizing 16 female Yorkshire pigs in a series of eight heart transplant procedures under a circulatory death model. Results: Successful resuscitation of the donor hearts occurred in seven out of eight animals. All seven of these hearts were deemed to have good function and were successfully transplanted. In the animal in which donor heart resuscitation was not successful, the transplant was aborted, and a left ventricular assist device (LVAD) was placed in the recipient's heart. Conclusion: This animal study demonstrates the feasibility of using this novel technique for resuscitation and precardiectomy evaluation of donated after circulatory death hearts. For those donor hearts without adequate function, an LVAD can be safely implanted as a "bail‐out" option. The limitations of this technique are the patient population to which it can be applied (only those patients eligible and consented for LVAD).